Analisis Sentimen Aplikasi Primaku Menggunakan Algoritma Random Forest dan SMOTE untuk Mengatasi Ketidakseimbangan Data - Riska Aryanti; Titik Misriati; Asriyani Sagiyanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Primaku application is an application that can be used as a tool to monitor the growth of children under five, this application can be used to collect data on the growth of children under five, apart from that this application can also provide clear information and visualization about the growth of children under five, including nutritional status and growth development In accordance with the standards that have been set, the Primaku application can help parents or health workers in routinely monitoring the growth of children under five and early detecting the potential risk of stunting. Stunting is a growth disorder that occurs in children under five due to malnutrition which is characterized by the child's height. which is shorter than the age standard. Stunting can have a long-term impact on a child's quality of life, such as disrupting physical, cognitive and social development, as well as increasing the risk of chronic disease in adulthood. The primaku application has been widely used, more than 500,000 users have downloaded this application and 44,700 reviews have been given by users to this application, however, reading all the reviews may take time, but if there are few reviews read, then the review results will be biased. Therefore, sentiment analysis aims to overcome this problem by automatically grouping user reviews into positive and negative reviews. Therefore, research on toddler growth detection to determine the public's response to the Primaku application can be of great benefit in efforts to prevent stunting in children under five in Indonesia. In this research, the random forest algorithm with the SMOTE technique was used to carry out sentiment analysis of Primaku application reviews. The random forest algorithm is a machine learning algorithm based on decision trees. The SMOTE technique is used to overcome data imbalance problems and is able to reduce overfitting while increasing the performance of the Random Forest algorithm. The data used in this research is Primaku application review data obtained from scrapping results from the Google Play Store. This data contains comments from application users, namely positive and negative. The results of this sentiment analysis show a deep understanding of user perceptions of the Primaku application. This sentiment analysis can be a basis for further improvement and development of the Primaku application, with a focus on aspects that influence user satisfaction and the research results show that the random forest algorithm with the SMOTE technique can produce quite good accuracy in sentiment analysis of the Primaku application. obtained in this study was 88%.